2004
DOI: 10.1002/cncr.20404
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the small bowel

Abstract: Trio, a member of the Dbl family of guanine nucleotide exchange factors (GEFs), has a series of spectrin repeats, two GEF domains, protein interaction domains, and a putative kinase domain, potentially important in neuronal axon guidance and cell migration. Most knowledge about Trio is based on studies of Caenorhabditis elegans and Drosophila, while the function of Trio in vertebrates is unclear. The aim of these experiments was to establish the patterns of Trio expression in the postnatal rat brain. During po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
168
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(202 citation statements)
references
References 73 publications
10
168
1
2
Order By: Relevance
“…In agreement with previous findings [5,7,13,14,19], we found that relapse occurred at distant sites (100%) but not at locoregional sites (0%). Despite our finding that systemic adjuvant therapy did not enhance RFS or OS, the failure patterns we observed strongly support further investigations of systemic adjuvant therapy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with previous findings [5,7,13,14,19], we found that relapse occurred at distant sites (100%) but not at locoregional sites (0%). Despite our finding that systemic adjuvant therapy did not enhance RFS or OS, the failure patterns we observed strongly support further investigations of systemic adjuvant therapy.…”
Section: Discussionsupporting
confidence: 82%
“…The factors associated with a poor prognosis in patients with SBA are duodenal location [11,12,13], poor differentiation [11,12], non-curative resection or positive margins [5,7,12,14,15], T 4 tumor stage [5,12], TNM stage [11,13,16], and lymph node involvement [12,14,15,17]. Among our patients, poor differentiation and lymph node involvement were statistically significant indicators of a poor prognosis in univariate analysis, with lymph node involvement being the sole prognostic factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of tumor response (and treatment toxicity) often relied on heterogeneous, obsolete criteria (e.g., clinical examination) [16]. In the most recently published and largest series of 217 patients with SBA (74% with stage III–IV disease) who were registered at the MD Anderson Cancer Center (Houston, Tex., USA) between 1978 and 1998, only 48 (22%) received palliative chemotherapy; however, no details regarding regimens used, efficacy and toxicity were provided [17]. A retrospective series recently reported in abstract form showed that only 14 of the 37 patients with advanced SBA seen in a 10-year period at the BC Cancer Agency received palliative chemotherapy; 19 different palliative-intent regimens, most including a fluoropyrimidine, were used, and resulted in tumor response in 2 patients (response rate 5%): in 1 after infusional 5-FU in the first-line setting, and in 1 after second-line irinotecan [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have concluded that only surgical resection can provide a better prognosis, and that completely or potentially curative resection and positive lymph nodes are of major prognostic significance in SBA. 3,5,6 Therefore, it is important to detect SBA at a stage when curative resec-…”
Section: Introductionmentioning
confidence: 99%